2022
DOI: 10.3389/fonc.2022.982461
|View full text |Cite
|
Sign up to set email alerts
|

Five-year relative survival by stage of breast and colon cancers in northern Italy

Abstract: The aim of this study is to present the 5-year relative survival by stage of breast and colorectal cancer patients in a northern Italian province. For the period 2013-2015, cases were selected from the Reggio Emilia Cancer Registry. Breast cancer patients were divided into 3 age groups: <45, 45-74 (the target screening population) and 74+. Colorectal cancers patients were classified into <50, 50-69 (the target screening population), and over 69 years. Carcinomas in situ and unknown stage were bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Finally, adipose tissue parameters were collected using a CT scan, which is a routine imaging examination in rectal cancer staging and is considered a de facto gold standard method for evaluating body composition, especially for conducting abdominal body fat measurements in patients with rectal cancer [ 29 , 30 ]. The exclusion of stage I rectal cancer patients, who lacked a routine baseline staging CT scan, should not have led to a relevant loss of events, given the high survival of stage I patients, i.e., over 96% 5-year relative survival in our province [ 31 ]. However, some stage shift phenomenon can occur if patients are staged with different accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, adipose tissue parameters were collected using a CT scan, which is a routine imaging examination in rectal cancer staging and is considered a de facto gold standard method for evaluating body composition, especially for conducting abdominal body fat measurements in patients with rectal cancer [ 29 , 30 ]. The exclusion of stage I rectal cancer patients, who lacked a routine baseline staging CT scan, should not have led to a relevant loss of events, given the high survival of stage I patients, i.e., over 96% 5-year relative survival in our province [ 31 ]. However, some stage shift phenomenon can occur if patients are staged with different accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Kittrongsiri et al ( 29 ) showed the 5-year OS of stage I–IV CRC patients were 79.67, 67.50, 44.77, and 11.02%, respectively. Mangone et al ( 30 ) found that the 5-year survival of colon cancer was 96.7, 83.4, 70.8, and 16.2%. In our study, the 5-year PFS/OS of stage I–IV CRC patients were (PFS: 78.52, 69.17, 47.04, and 7.30%; OS: 81.34, 71.67, 50.37, and 8.76%).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous initiatives are introduced in different countries to find out mechanisms for the reimbursement and funding of new medicines (32). To overcome the aforementioned barriers and to foster market and patient access, some countries developed methodologies for new market access agreements to reduce the financial burden and cost of uncertainty to public payers by sharing the risk between the payer and the manufacturer (6).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis in the early stages increases the 5-year relative breast cancer survival rates-−99% for localized tumors and 86% for regional cancer, but, for advanced stages, the breast cancer survival rate falls below 30% (5). The established 5-year breast cancer survival rates in Italy are 100, 89.7, 71.4, and 29.1% for stages I, II, III, and IV, respectively (6). Epidemiological data show that 15-10% of the newly diagnosed patients are found to have a metastatic (advanced) disease and 20-30% of the early diagnosed patients are expected to have a metastatic relapse over time (7,8).…”
mentioning
confidence: 99%